2016
DOI: 10.1039/c5ee03404c
|View full text |Cite
|
Sign up to set email alerts
|

A flexible solid-state electrolyte for wide-scale integration of rechargeable zinc–air batteries

Abstract: Replacing liquid electrolytes with a versatile, solid-state membrane based on highly functionalized cellulose nanofibers allows for easy integration of rechargeable zinc–air into any bendable and wearable devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
255
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 290 publications
(267 citation statements)
references
References 50 publications
2
255
0
Order By: Relevance
“…[6] However, in portable applications, their merits are largely limited by the bulky battery configurations, as a result of relying on aqueous electrolytes. [7,8] To this end, one approach is to swap aqueous electrolytes for versatile, solid-sate alternatives, making zinc-air batteries safer, lighter, and more portable. The main issues related to the solid-state electrolytes are insufficient ionic conductivity, electrolyte retention, and complex synthesis process.…”
Section: Doi: 101002/aenm201600476mentioning
confidence: 99%
See 1 more Smart Citation
“…[6] However, in portable applications, their merits are largely limited by the bulky battery configurations, as a result of relying on aqueous electrolytes. [7,8] To this end, one approach is to swap aqueous electrolytes for versatile, solid-sate alternatives, making zinc-air batteries safer, lighter, and more portable. The main issues related to the solid-state electrolytes are insufficient ionic conductivity, electrolyte retention, and complex synthesis process.…”
Section: Doi: 101002/aenm201600476mentioning
confidence: 99%
“…[19] Meanwhile, due to its highly reactive area rich in hydroxyl groups, cellulose can be easily refashioned through a surface-functionalization to conduct ions and be utilized in advanced batteries. [7] Herein, for the first time, we report on a laminate-structured nanocellulose/GO membrane functionalized with highly hydroxide-conductive quaternary ammonium (QA) groups to be applied as a robust solid-state electrolyte in flexible, rechargeable zinc-air batteries. The QA-functionalized nanocellulose/GO (QAFCGO) membrane is fabricated through chemical functionalization, layer-by-layer filtration, cross-linking, and ion-exchange processes (Figure 1a).…”
mentioning
confidence: 99%
“…An adaptable negative potential (−0.762 V vs. SHE)19, enable it to be constructed with other cathodes in aqueous electrolytes. Several rechargeable zinc batteries, including nickel//zinc battery20, zinc//air battery21 and Zn//Na 0.95 MnO 2 7, Zn//LiMn 2 O 4 822 have been investigated in aqueous systems.…”
mentioning
confidence: 99%
“…The monoclinic Li 3 V 2 (PO 4 ) 3 and rhombohedral Na 3 V 2 (PO 4 ) 3 have attracted considerable interest as promising cathode candidate in non-aqueous lithium-ion batteries due to their thermodynamically stable structure, high cell-voltage and fairish theoretical specific capacity (LVP: 191 mAh g −1 for extraction of three Li + ions between 3.0–4.6 V, 133 mAh g −1 for extraction of two Li + ions between 3.0–4.2 V vs. Li + /Li; NVP: theoretical discharge capacity with 118 mAhg −1 , with two Na + ions being completely extracted up to 4.0 V versus Na + /Na) 192021222324…”
mentioning
confidence: 99%
“…Such batteries are freed from the constraints of rigidity and weight that characterize current portable batteries. [9][10][11][12][13][14][15] Companies working in rechargeable, polymer Zn-MnO 2 batteries have demonstrated that this new zinc secondary battery chemistry is well suited to a broad range of features for flexible electronics at reduced cost. To provide a power source for these applications, flexible batteries delivering a high volumetric energy density are particularly desirable because there is often a limited volume for integrating the batteries into these applications.…”
Section: Introductionmentioning
confidence: 99%